Seroprevalence survey of arboviruses in workers from Tuscany, Italy - Remoli, Maria Elena; Fiorentini, Cristiano; Marchi, Antonella; Di Renzi, Simona; Vonesch, Nicoletta; Peri, Maria Vittoria; Bastianini, Lucia; Rossi, Sonia; Bartoccini, Giulia; Kuttappasery, Maya Lissa; Ciufolini, Maria Grazia; Tomao, Paola (La Medicina del Lavoro, 2018)
Background: Arthropod-borne viruses (Arbovirus) play an important role among emerging and re-emerging infectious diseases and in the spreading of infections in new geographic areas. Although some arboviral infections may be asymptomatic or mild flu-like illnesses, many occur as severe forms of meningitis and meningoencephalitis. Objectives: To assess whether arboviral infections may be associated with occupational risk, in a population of agricultural and forestry workers potentially at high risk for arthropods bite and sting. Methods: A seroprevalence survey for arboviruses belonging to the genera Flaviviruses (West Nile, Tick-borne encephalitis and Usutu viruses) and Phlebovirus (Toscana virus) was carried out in Grosseto province (Tuscany, Italy). One hundred and one serum samples of occupationally exposed workers and 100 serum samples of not exposed workers were analyzed using commercial and home-made serological assays. Serological data were obtained in 2012 and analyzed according to demographic characteristics, recollection of insect-bites, and time spent in outdoor activities. Results: A total seropositivity of 10% (21/201) was observed for Toscana virus. No difference in seroprevalence for Toscana virus was observed among the exposed (10/101) versus the not exposed (11/100) workers. No seropositivity for West Nile, Usutu and Tick-borne encephalitis viruses was detected. Conclusions: Although circulation of Toscana virus is recognized in the study area, our results did not reveal a higher risk for workers exposed to arthropods bite and sting. Health surveillance programs remain useful to monitor the potential emergence of arboviruses.